Analisis Pengakuan, Pengukuran, dan Pengungkapan Pendapatan Pada Platform Digital Ride-Hailing Berdasarkan PSAK 72 - Alif Luqmanul Hakim; Yuniarwati Yuniarwati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyse the appropriateness of the recognition, measurement, and disclosure of revenue by PT GoTo Gojek Tokopedia Tbk in accordance with PSAK 72, and to determine the company’s role as a principal or agent in ride-hailing transactions. The study employs a qualitative approach using the case study method. Data were obtained from the consolidated financial statements and annual reports of PT GoTo Gojek Tokopedia Tbk, which were analysed by comparing the company’s accounting policies with the provisions of PSAK 72. The results indicate that revenue is recognised when the performance obligation is satisfied, whilst revenue measurement employs the net revenue approach, namely the amount of commission or service fees to which the company is entitled. Revenue disclosure also complies with PSAK 72 through the presentation of information regarding gross revenue, net revenue, Gross Transaction Value (GTV), and revenue segmentation. Furthermore, PT GoTo Gojek Tokopedia Tbk is more appropriately classified as an agent as it does not control the transport services before their transfer to customers. Consequently, the application of PSAK 72 has reflected the economic substance of the transactions and enhanced the transparency and relevance of the information in the financial statements.